2018
DOI: 10.1016/j.biopsych.2016.12.023
|View full text |Cite
|
Sign up to set email alerts
|

Beta-Site Amyloid Precursor Protein Cleaving Enzyme 1 Inhibition Impairs Synaptic Plasticity via Seizure Protein 6

Abstract: Our results suggest that SEZ6 plays an important role in maintaining normal dendritic spine dynamics. Furthermore, SEZ6 is involved in BACE1 inhibition-induced structural and functional synaptic alterations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
98
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 91 publications
(101 citation statements)
references
References 62 publications
(97 reference statements)
3
98
0
Order By: Relevance
“…Although associated with β‐cleavage of APP, leading to greater Aβ and βCTF expression, attenuation of Bace1 levels by MCS may indicate a counterintuitive normalization of APP processing in vulnerable neurons that reflects the importance of steady‐state Aβ and βCTF levels, underscoring the importance of evaluating βCTF expression in DS/AD models (Jiang et al, ). Alternatively, Bace1 deficiency may be considered detrimental, as a loss of Bace1 expression impairs myelination (Hu, Hu, Dai, Trapp, & Yan, ) and causes hippocampal synaptic deficits (Petrus & Lee, ; Wang et al, ; Zhu et al, ), illustrating the need for normative Bace1 levels. MCS also restores the normal expression of two truncated forms of tau ( Mapt2N6D and Mapt2N6P ).…”
Section: Discussionmentioning
confidence: 99%
“…Although associated with β‐cleavage of APP, leading to greater Aβ and βCTF expression, attenuation of Bace1 levels by MCS may indicate a counterintuitive normalization of APP processing in vulnerable neurons that reflects the importance of steady‐state Aβ and βCTF levels, underscoring the importance of evaluating βCTF expression in DS/AD models (Jiang et al, ). Alternatively, Bace1 deficiency may be considered detrimental, as a loss of Bace1 expression impairs myelination (Hu, Hu, Dai, Trapp, & Yan, ) and causes hippocampal synaptic deficits (Petrus & Lee, ; Wang et al, ; Zhu et al, ), illustrating the need for normative Bace1 levels. MCS also restores the normal expression of two truncated forms of tau ( Mapt2N6D and Mapt2N6P ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, Zhu et al tried in their work to explore whether BACE1 inhibition is causing synaptic dysfunction due to perturbation in SEZ6 function. Thus, it was demonstrated that prolonged BACE1 inhibition using potent inhibitor like NB‐360 was only causing reversible spinal density reduction in wild type mice (control) while such effect was not seen in SEZ6 knockout mice group . Moreover, synaptic impairment caused by BACE1 inhibition was prevented by knocking out SEZ6 from matured neurons .…”
Section: Failure Of Bace1 Inhibitors: Lessons To the Futurementioning
confidence: 99%
“…On the other hand, though, the levels of the substrate candidate NLGN2 would be expected to be increased as well and may sequester the increased MDGA1 levels, thus not resulting in a change in inhibitory synapse formation. Yet, other BACE1 substrates, such as SEZ6, voltage‐gated sodium channels, Jagged, and Nrg1, also affect directly or indirectly synaptic transmission . Thus, synaptic alterations in BACE1‐deficent mice may not be attributed easily to individual substrates, but may reflect complex changes in the function of multiple substrates.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, other BACE1 substrates, such as SEZ6, voltage-gated sodium channels, Jagged, and Nrg1, also affect directly or indirectly synaptic transmission. [25][26][27][28]32,78,79 Thus, synaptic alterations in BACE1-deficent mice may not be attributed easily to individual substrates, but may reflect complex changes in the function of multiple substrates.…”
Section: Discussionmentioning
confidence: 99%